Conventional versus reference-surface mass balance - Huss, Matthias; id_orcid:0 000-0002-2377-6923; Hock, Regine; Bauder, Andreas; id_orcid:0 000-0001-7197-7706; Funk, Martin (Journal of Glaciology, 2012)
ISSN:0022-1430 ISSN:1727-5652